The Office of Digital Humanities Turns Ten. - Hindley, Meredith (Humanities)
The article offers information about the National Endowment for the Humanities (NEH) that grants supported scholars using punch cards and statistical methods to create compendiums and answer literary questions. It mentions that NEH supports digital humanities projects, particularly for younger scholars. It also mentions that NEH Chairman Bruce Cole gave the go-ahead to create the Office of Digital Humanities (ODH) in 2008 with Brett Bobley serving as its director.